Generalized Coherent Photogalvanic Effect in Coherently Seeded Waveguides. Issue 12 (14th September 2022) - Yakar, Ozan; Nitiss, Edgars; Hu, Jianqi; Brès, Camille‐Sophie
Abstract: The coherent photogalvanic effect leads to the generation of a current under the absorption interference of coherent beams and allows for the inscription of space‐charge gratings leading to a second‐order susceptibility (χ (2) ). The inscribed grating automatically results in quasi‐phase‐matching between the interfering beams. Theoretical and experimental studies, considering the degenerate case of second‐harmonic generation, show significant conversion efficiency enhancements. However, the link between the theory and experiment is not fully established such that general guidelines and achievable conversion efficiency for a given material platform are still unclear. In this work, the phenomenological model of coherent photogalvanic effect in optical waveguides is theoretically analyzed. This model predicts the existence of non‐degenerate sum‐frequency generation quasi‐phase‐matching gratings, which is confirmed experimentally for the first time. Furthermore, the time dynamics of the space‐charge grating inscription in coherent photogalvanic process is formulated. Based on the developed theoretical equations, the material parameters governing the process for stoichiometric silicon nitride are extracted. The results obtained provide a basis to compare the performances and potentials of different platforms. This work not only supplements the theory of coherent photogalvanic effect, but also enables us to identify critical parameters and limiting factors for the inscription of χ (2)  gratings. Abstract : Novel theoretical and experimental results on the coherent photogalvanic effect in nonlinear optical waveguides are presented. The established general framework provides means for unlocking nonlinear effects in integrated photonic devices made of centrosymmetric materials after inducing efficient and exploitable second‐order nonlinear susceptibility via coherent currents. This work also serves as a foundation for comparing the potentials of various material platforms.